A numerical study on the separation of droplet on the heterogeneous surface. (18th July 2017) - Lee, Soon Ho; Son, Sung Wan; Choi, Ho Yeon; Park, Sang-Hu; Ha, ManYeong
Highlights: The separation of droplet located on a heterogeneous surface is analyzed. All reviewer's comments are considered in revised manuscript. The grid dependency test are conducted and its results are attached in rebuttal letter. Our mistakes is corrected in revised manuscript. Abstract: The behavior of the hemispherical droplet existing on a heterogeneous surface was investigated using a 3-D Lattice Boltzmann method. This study considered the shape where a rectangular hydrophobic surface with width is l and vertical length L exists at the center of a square bottom surface, which is relatively hydrophilic, and of which the length of one side is L . The hydrophilic surfaces on the left and right sides separated by the hydrophobic surface have different contact angles of θ 1 and θ 2 respectively, while the hydrophobic surface located between two hydrophilic surfaces has a contact angle of θ 3 . The contact angles θ 1 and θ 2 of two different hydrophilic surfaces considered are in the range from 20° to 70°, while the contact angle θ 3 of hydrophobic surface considered is in the range from 120° to 170° Whether the droplet is separated or not and the separation time depend on the sizes of the contact angles θ 1 and θ 2 of the two hydrophilic surfaces separated by a rectangular hydrophobic surface and the contact angle θ 3 of the hydrophobic surface. The times spent for separation and movement also depend on the size of the contact angle of each bottom surface, which also has an effect on the amount of the droplet being separated and divided.